STRATEGI IKLAN ADSENSE UNTUK AKSELERASI “UMKM GOES DIGITAL” - Lova Endriani Zen; Yunita Rahmasari; Yulaikha Mar’atullatifah; Dwi Utari Iswavigra; Nimas Ratna Sari (Bajang Institute, 2023)
The rapid development of social media platforms has encouraged the trend of social media marketing. Nowadays, many business owners use social media to market their products online. However, out of a total of 59.2 million MSMEs in Indonesia, only about 8% have used social media platforms to promote their products. Therefore, this community service aims to provide information on how to use Facebook Ads, Instagram Ads, TikTok Ads, and Youtube Ads platforms as well as the information about the effect of product photos and marketing language to boost sales for MSMEs owners in Solo area, Central Java. Participants were benefited with the information needed to apply AdSense ads in the designated popular social media platforms. For participants categorized as the digital immigrant group, they need more intensive assistance in understanding in depth how to implement the AdSense ads, potentially due to their age and digital literacy constraints.